Can Metaphorical Thinking Learning Model Enhance Students' Mathematical Literacy in Area Conservation? - Wahyuningtyas , Lilis; Amir, Mohammad Faizal (Journal of Integrated Elementary Education, 2025)
Primary students often face challenges with mathematical literacy. One practical approach to overcoming these challenges is the metaphorical thinking learning model, which utilizes metaphors to help students better visualize and grasp mathematical concepts. This study seeks to determine the impact of the metaphorical thinking learning model on students' mathematical literacy, particularly in the context of area conservation. For this research, we adopted a post-test-only control group design involving experimental and control groups with fourth-grade students. Participants were selected using a simple random sampling method. We collected data through a testing instrument designed to evaluate the students' mathematical literacy skills. The analysis used an independent t-test, preceded by normality and homogeneity tests, to ensure the data met the necessary prerequisites. The findings revealed a significant difference in mean scores, with the significance value falling below 0.05. This indicates that the metaphorical thinking learning model positively influences students' mathematical literacy. The results emphasize the model's effectiveness in enhancing the mathematical literacy of primary students. Furthermore, this study substantially affects various aspects of mathematical literacy. The areas most notably improved include the ability to formulate mathematical situations, followed by employing concepts, facts, procedures, and reasoning. The least affected aspects were interpreting, applying, and evaluating mathematical outcomes.